Understanding the pitch and overtone of slenthem (Indonesian metallophone in Javanese gamelan orchestra) using audio-based approaches through Fast Fourier Transform (FFT). - Musib, Ahmad Faudzi; Hamdan, Sinin; Sinin, Aaliyawani Ezzerin; Mohamad Said, Khairul Anwar; Sawawi, Marini; Sosiati, Harini (Taylor's University, 2024)
This paper discusses the fundamental and overtone frequencies of slenthem (Indonesian metallophone in Javanese gamelan orchestra) using audiobased approach through Fast Fourier Transform (FFT). The fundamental and overtone frequencies for each plate enables the determination of the key in the slenthem. The finding indicates that the plates 1, 2, 3, 5, 6, and 1' for slenthem from the Faculty of Applied and Creative Art (FACA) of Universiti Malaysia Sarawak (UNIMAS) are A2#, D3#, F3, G3, A3#, and C4#, respectively, while slenthem from the Badan Budaya Unimas (BAYU) is B2, C3, D3#, F3, G3, and A3 respectively. The plate has an individual tube resonator with various opening sizes and air column depths. The effects of the opening and air column were studied by changing the tube resonator of each plate. The plate determines the frequency of the slenthem, not the opening sizes or the length of the air column inside the tube resonator. The sound produced by the plate with and without a tube resonator were carried out to check the effect of the air column inside the tube resonator. The PicoScope determine the frequency using FFT and Adobe Audition analysing the frequency that leads to time-frequency analysis (TFA).